STRATEGI KOMUNIKASI ANTARPRIBADI CRO DALAM MEMBANGUN KEPERCAYAAN PELANGGAN DI PT ASTRA DAIHATSU CIBEUREUM BANDUNG - Genik Puji Yuhanda; Taufik Furqon Nurhakim; Adi Muhammad Ramadhan (Jurnal Ranah Komunikasi, 2026)
PT Astra Daihatsu Cibeureum Bandung is a profit-oriented company operating in the automotive sector. In the midst of tight business competition, product quality needs to be supported by good service quality. The party whose job it is to serve and foster good relationships with customers is the customer relations officer (CRO). To grow customer trust, an interpersonal communication strategy is needed by the CRO which prioritizes the principles of being a good listener, empathy, honesty and openness of information, communicativeness and solutions. This research uses a qualitative approach with a descriptive study. The theory used is the symbolic interaction theory of George Herbert Mead. The data collection techniques used were interviews, observation and literature study. The results of the research show that the interpersonal communication strategy carried out by CRO has fostered trust in customers, thereby creating mutual benefits and satisfaction. This research also contributes to solving practical problems, especially related to interpersonal communication carried out by company members with their customers.